PERAN PEMERINTAH KABUPATEN GRESIK DALAM KEMITRAAN BERBASIS CORPORATE SOCIAL RESPONSIBILITY - Kurnia Eka Pratiwi, Nuraida Muji; ', Sutomo '; ', Dina Suryawati (Jurnal Ilmu Administrasi Negara, 2014)
The Role of Government in Gresik Based Partnership Corporate Social Responsibility (CSR). This study aims to describe the implementation of CSR-based partnership program by PT. Semen Gresik and Government’s role in optimizing the partnership. This research approach is qualitative approach with descriptive type, while the data analysis is to use interactive model. The results showed that the CSR program partnership model adopted by PT. Semen Gresik venture philanthropy partnerships using the plasma core, but the partnership is still pseudo partnership and the role of government in optimizing partnerships Gresik still be mandating and partnering, in the form of a mandate to form a company with a team sub-district and district level coordination to KISS (coordination, integration, synchronization, and synergy). However, the role of facilitating and endorsing yet implemented, so that such a partnership can not be optimized. Keywords: corporate social responsibility, the partnership, the role of government, coordination.